Health Promotion toward Knowledge and Intention for Early Detection of Cervical Cancer in Commercial Sex Workers - Rusmiati, Desi; Silitonga, Tiurlan Yunetty; Warendi, Warendi (Kesmas, 2018)
Cervical cancer is one of the cancer types that become a haunting danger for many women in the world. In Indonesia, the prevalence rate reached 0.8% or an estimated 98,692 patients. Its prevalence increased to 10% in the commercial sex worker group. This study aimed to explain the effect of health promotion on knowledge and intention for early detection of cervical cancer using the inspection of visual acetate method in the commercial sex workers. This study was quantitative with a quasi-experimental type, one group of pretest and posttest design. The population sample included the commercial sex workers at Genteng Subvillage, Patimban Village, Pusakanegara Subdistrict, Subang District and was determined by using an accidental sampling technique with 35 respondents. Data analysis used McNemar's test. The results showed that there was an increase in knowledge after the health promotion activity and a significant change in intention to perform early detection of cervical cancer. From the statistical test, a p value of 0.000 was obtained for each variable. In conclusion, health promotion has a significant effect on the improvement in the knowledge and intention of the respondents.